MANAGING THE PRODUCTIVITY PROCESS IN AGRICULTURE, A FRAMEWORK FOR IMPROVING THE MARKET POSITION OF AGRICULTURE OF THE REPUBLIC OF SRPSKA - Čekrlija, Saša; Đuričić, Zoran; Jovanović, Radomir; Pešević, Slobodan (Economics of Agriculture, 2023)
Agriculture in Republika Srpska is the second largest sector with products of low added value. The biggest challenge is strengthening resilience and increasing competitiveness in the market. This paper analyzes the possibilities for improving the position of small farms and establishing a framework for more efficient development of entrepreneurship in the agricultural sector of the Republic of Srpska. The methods used in agro-economic research are used in the work, namely description, induction, deduction, synthesis, compilation, and data comparison and analysis. The increase in productivity is directly dependent on the diversification of production, the application of positive practices and increased resistance to climate change. Improved safety standards of agricultural products and food quality directly affect increased competitiveness and the potential for access to higher value markets. The application of climate-smart irrigation technologies and the improvement of water management in agriculture represents a revolutionary turning point in agriculture.